SISTEM INFORMASI PEMESANAN MINUMAN PADA PT. MILL GILLINDO DJAYA - Maria Sin Eko Korebima; Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1998)
Manual system which took place at PT.MILL GILLINDO DJAYA efficient and effective in operation. With existence of computerized systems can reduce the constraints that exist and can increase work efficiency and effectiveness in PT.MILL GILLINDO DJAYA.